2015
DOI: 10.1002/jms.3614
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution MALDI‐TOF MS study on analysis of low‐molecular‐weight products from photo‐oxidation of poly(3‐hexylthiophene)

Abstract: High-resolution matrix-assisted laser desorption/ionization (MALDI) time-of-flight mass spectrometry (TOF MS) was used for the analysis of the low-molecular-weight products from the photo-oxidation of poly(3-hexylthiophene) (P3HT) in solution and thin film. Eight new peak series were observed in the low-mass range of the mass spectra of the products degraded in solution, and the formulas of the eight components were determined from the accurate mass. From SEC/MALDI-TOF MS, two components were identified as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…For the irradiated P­(ProDOT) films, both neutral and charge carrier absorbances showed a slight blue shift compared to the pristine film (80–100 nm, 0.15 eV for the near-IR peak and 20 nm for the neutral peak, 0.2 eV). Blue shifting absorbance peaks are characteristics of a decrease in effective conjugation length in a conjugated polymer as has been shown for irradiation studies in solution where substantial chain fragmentation was observed . The right electrode absorbance showed a similar trend in terms of the blue shift of the neutral state absorption (10–23 nm) and also showed a peak in the near-infrared at longer wavelengths (865–955 nm), likely due to a partially de-doped underlying PEDOT:PSS electrode.…”
Section: Results Sectionsupporting
confidence: 55%
See 1 more Smart Citation
“…For the irradiated P­(ProDOT) films, both neutral and charge carrier absorbances showed a slight blue shift compared to the pristine film (80–100 nm, 0.15 eV for the near-IR peak and 20 nm for the neutral peak, 0.2 eV). Blue shifting absorbance peaks are characteristics of a decrease in effective conjugation length in a conjugated polymer as has been shown for irradiation studies in solution where substantial chain fragmentation was observed . The right electrode absorbance showed a similar trend in terms of the blue shift of the neutral state absorption (10–23 nm) and also showed a peak in the near-infrared at longer wavelengths (865–955 nm), likely due to a partially de-doped underlying PEDOT:PSS electrode.…”
Section: Results Sectionsupporting
confidence: 55%
“…Blue shifting absorbance peaks are characteristics of a decrease in effective conjugation length in a conjugated polymer as has been shown for irradiation studies in solution where substantial chain fragmentation was observed. 42 The right electrode absorbance showed a similar trend in terms of the blue shift of the neutral state absorption (10−23 nm) and also showed a peak in the near-infrared at longer wavelengths (865−955 nm), likely due to a partially de-doped underlying PEDOT:PSS electrode. In addition to the shifts of the absorbance peaks, the P(ProDOT) from irradiated devices was rendered insoluble in toluene as shown in Figure S9 where the pristine sample dissolved immediately, and the irradiated samples were undissolved after a 10 min soak.…”
Section: ■ Introductionmentioning
confidence: 69%
“…DCTB is well-known for its efficient desorption/ionization capabilities at low laser fluences, which has been linked to its high molar absorption coefficient. 81 Its application range is somewhat limited, predominantly for analysis of polymers 82 , fullerens 83 , organometallics 84 and more recently nanoparticles and nanoclusters 85 . DCTB's mode of action in these applications is that of an aprotic, electron-transfer (ET) secondary reaction matrix, delivering primarily radical ions in positive ion mode, or, when purposely forced, cationized molecules of the investigated compounds.…”
Section: Resultsmentioning
confidence: 99%
“…A few reports have detected homocoupling defects using MALDI-TOF MS in CPs when using both conventional cross-coupling and DHAP techniques. , End group analysis and molecular weight determination of poly­(3-hexythiophene) (P3HT) is an area where MALDI-TOF MS has assisted with optimizing polymerization conditions and providing evidence for proposed mechanisms. More specifically, MALDI-TOF MS has aided with confirming a chain-growth mechanism in the Kumada catalyst-transfer polycondensation (CTP) method for the precise growth of P3HT by determining end group functionalization . With this end group control, there have been several reports regarding the incorporation of a variety of functional end groups such as phenyl, benzyl, vinyl, and allyl, which were all confirmed with MALDI spectra. , Additionally, MALDI-TOF MS has been used in determining the mechanism of photo-oxidized degradation in P3HT films through analyzing oxidized byproducts after illumination . Although P3HT is the most commonly studied conjugated polymer using MALDI-TOF MS, due to facile end group control, there have been other examples of using MALDI-TOF MS to determine end-capping efficiency in conventional metal-mediated step-growth type polymerizations. ,, …”
Section: Introductionmentioning
confidence: 99%